Effectiveness of Gamma Rays in Attenuating Rodent Malaria Parasites of Plasmodium berghei in Blood of Mice - M. Syaifudin; Darlina Darlina; T. Rahardjo; D. Tetriana; S. Nurhayati; H.N.E. Surniyantoro; T. Kisnanto (Atom Indonesia, 2013)
Malaria is a major public health problem in Indonesia. Therefore, an effective vaccine against this disease is actively being sought by using gamma rays to attenuate the parasites. However, the safety and efficacy of the resulting vaccine are dependent on the precise irradiation dose. The aim of this research was to determine the exact time when the parasites are attenuated by gamma ray exposure. Mice blood containing Plasmodium berghei of 5,0 X 107 parasites/ml was irradiated with gamma rays at doses of 0, 150, 175 and 200 Gy (doses rate of 380 Gy/h) and then was injected intraperitoneally to mice at 0, 1, 2, 3, and 4 h post irradiation. The parasitemia (parasite density) in mouse blood was observed starting with day 2 and repeated every 2-4 days up to 28 days. The survival of the mice was also observed during the experiment. The results showed that the pre-patent period advanced with exposing infected blood to 150 and 175 Gy irradiations, suggesting some degree of attenuation. The amount of radiation required to render the parasites non-viable is about 175 Gy for an inoculum of a number of parasites, but a delay of 4 h resulted in the death of parasites. There was no difference in the infectivity of irradiated parasite injected 1 h and 2 h post irradiation in terms of parasitemia and the survival of mouse. For a dose of 200 Gy which was injected 2 h post irradiation, no parasitemia was found in the blood and animals which died after times varying from 1 to 4 weeks. We concluded that irradiated parasites should be injected into the host within 1 h after irradiation.Received: 16 January 2013; Revised: 23 April 2013; Accepted: 24 April 2013